Recent advances in L-Asparaginase enzyme production and formulation development for acrylamide reduction during food processing - Arindam Jana; Soumyajit Biswas; Ritu Ghosh; Rahul Modak (Food Chemistry: X)
L-asparagine is an essential amino acid for cell growth and common constituent of all the proteins. During high temperature food processing it reacts with reducing sugars and leads to acrylamide production through a complex process known as Maillard reaction. L-asparaginase hydrolyses the amine-group of L-asparagine to produce aspartic acid and ammonia. L-asparaginase pre-treatment of potato led to more than 80 % reduction of acrylamide content in foods like french fries, potato chips and in flour-dough based products. New cost-effective strategies for large scale L-asparaginase production and diverse types of formulations will be needed to successfully integrate L-asparaginase in food processing. Here we comprehensively review the recent developments in enzyme production to enhance the yield, activity and specificity of L-asparaginase. Novel liquid and lyophilized formulations are developed to enhance stability and activity of the enzyme under different conditions. These developments present a promising approach to enzymatically mitigate acrylamide formation during food processing.